Intraoperative Transpedicular Onyx Injection to Reduce Vascularity of a Thoracic Hemangiopericytoma After Unsuccessful Preoperative Endovascular Embolization: a Technical Report. Issue 2 (10th May 2017) - Mashaly, Hazem; Zhang, Zoe; Shaw, Andrew; Youssef, Patrick; Mendel, Ehud
Abstract: BACKGROUND AND IMPORTANCE: Hemangiopericytoma is a rare vascular tumor with central nervous system involvement representing only 1% of central nervous system tumors. They rarely affect the vertebral column. Complete surgical resection is the treatment of choice for hemangiopericytoma given their high rates of local recurrence. However, the high vascularity of such tumors with the risk of massive bleeding during surgery represents a significant challenge to surgeons. Therefore, preoperative endovascular embolization via the transarterial route has been advocated. CLINICAL PRESENTATION: In the current study, we present a case of a T12 hemangiopericytoma that was managed by a 2-stage surgical resection, with the use of intraoperative transpedicular onyx injection to reduce intraoperative blood loss following an unsuccessful trial of preoperative endovascular embolization. CONCLUSION: Preoperative endovascular embolization is not feasible in some cases due to the location of the segmental or radiculomedullary arteries in relation to tumor feeders and, rarely, small size of these arterial feeders. Percutaneous injection of onyx is an option. In this case report, we discuss direct intraoperative injection via a transpedicular route as a safe and effective method for decreasing the vascularity of some lesions and improving intraoperative blood loss.